2008
DOI: 10.5194/acp-8-1609-2008
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft measurements of microphysical properties of subvisible cirrus in the tropical tropopause layer

Abstract: Abstract. Subvisible cirrus (SVC) clouds are often observed within the tropical tropopause layer (TTL). Some studies suggest that SVC has a significant impact on the earth radiation budget. The Costa Rica Aura Validation Experiment (CR-AVE) sponsored by the National Aeronautics and Space Administration (NASA) took place near San Jose, Costa Rica from 14 January–15 February 2006. The NASA WB-57F sampled SVC in the TTL from −75°C to −90°C with an improved set of cloud particle probes. The first digital images of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
150
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(175 citation statements)
references
References 47 publications
(75 reference statements)
22
150
3
Order By: Relevance
“…The two particle size distributions shown in Jensen et al (2016) extend to maximum dimensions of about 50 mm and almost 200 mm, at temperatures of ,195 K and between about 195 and less than 210 K, respectively. Meanwhile, Lawson et al (2008) report particle distributions extending to 165 mm in the subvisual TTL cirrus they sampled, which contrasts with the study of McFarquhar et al (2000), who found that particle maximum dimensions did not extend to beyond 50 mm. Determining the habit mixtures and particle distributions in TTL cirrus is important, as the choice of assumed particle distributions in climate models will influence their predicted radiative effect of cirrus.…”
Section: Introductioncontrasting
confidence: 67%
See 4 more Smart Citations
“…The two particle size distributions shown in Jensen et al (2016) extend to maximum dimensions of about 50 mm and almost 200 mm, at temperatures of ,195 K and between about 195 and less than 210 K, respectively. Meanwhile, Lawson et al (2008) report particle distributions extending to 165 mm in the subvisual TTL cirrus they sampled, which contrasts with the study of McFarquhar et al (2000), who found that particle maximum dimensions did not extend to beyond 50 mm. Determining the habit mixtures and particle distributions in TTL cirrus is important, as the choice of assumed particle distributions in climate models will influence their predicted radiative effect of cirrus.…”
Section: Introductioncontrasting
confidence: 67%
“…The balance between cirrus warming or cooling the upper troposphere depends on its visible optical depth, as shown by Hong and Liu (2015), who demonstrated that cirrus with visible optical depths less than unity leads to a net heating of the upper troposphere, while optically thicker cirrus results in a net cooling of the upper troposphere. Moreover, subvisual cirrus occurs in the TTL, as found by Lawson et al (2008); also, Lee et al (2009) showed that these clouds may exert a net radiative effect on the order of about 1.1 W m 22 .…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations